Effect of the Y2O3 amount on the oxidation behavior of ZrB2-SiC-based coatings for carbon/carbon composites. Issue 12 (September 2022) - Lin, Hao; Liu, Yangyang; Liang, Wenping; Miao, Qiang; Zhou, Shaoyun; Sun, Jiayu; Qi, Yan; Gao, Xiguang; Song, Yingdong; Ogawa, Kazuhiro
Abstract: In this paper, the effect of Y2 O3 addition on the oxidation resistance of ZrB2 -SiC-Y2 O3 coating for the SiC coated carbon/carbon composites was investigated. Results confirmed the great benefits of adding Y2 O3 to the oxidation-resistant properties of the original coating from different aspects. The dense structure of surface and cross-section and formation of yttria stabilized zirconia, Y2 Si2 O7, t-ZrO2 phases were observed after adding Y2 O3 . Additionally, according to the TEM results, yttrium silicate existed in the form of nanoparticles, while yttria stabilized zirconia existed in the form of agglomeration within the SiO2 liquid phase. This superior oxidation resistance was attributed to the following reasons: (i) the formed Zr-Si-Y-O glass barrier layer blocked the oxygen diffusion and healed the cracks; (ii) the reduced m-ZrO2 content weakened the volume expansion of the coating and avoided spallation; (iii) Y2 Si2 O7 served as a pinning phase which modified the stability of liquid SiO2 at elevated temperatures. Highlights: The addition of Y2 O3 effectively improved the oxidation resistance of ZrB2 -SiC coatings at 1773 K. The microstructural evolution of the composite coatings after oxidation was investigated. The stability of SiO2 glass at elevated temperature was improved by introducing Y2 O3 . The oxidation mechanism of the composite coatings with different Y2 O3 contents was revealed.